Reproliferation of Islamist Movement in Surakarta: Trajectory and Strategy in The Post Democratization Indonesia - Duraesa, Muhammad Abzar; Ahyar, Muzayyin (IAIN Surakarta, 2019)
Islamist movement has been proliferating in line with the historical trajectory of Indonesia's political journey; starting from the colonial regime, in the beginning of independence, New Order regime and today’s Era Reformasi. The process of Democratization and modernization lead the ideology of Islamism to a new phase of religious movement. Along with the growth of democracy in Indonesia, Islamist movement precisely shows its existence intensely in public sphere. The opening canals of freedom in the Reformation Era became a new space for ideology of Islamism to evolve and adapt some strategies to survive amidst the onslaught democratization in Indonesia. This article aims at looking to what extent the proliferation of Islamist movements after the collapse of Soeharto’s authoritarian regime in Indonesia. In this case, Surakarta becomes important to observe because it’s historical context as an embryo in giving birth to earlier Islamist movements, as well as a city famous for the proliferation of ideology of Islamism in Indonesia. Using political sociology approach, this study attempts to understand the path of proliferation of Islamist movements and its various interplayed strategies to the socio-political conditions that occur; either on a global or local scale. This article argues that the development of democracy in Indonesia continues to alter the route map of the Islamist movement. Finally, the results of this study reveal that the proliferation of the current Islamist movement plays a new strategy that appropriated with the development of democracy and technological advancements to gain more public sphere by Indonesian people.